Socio-Ecological Readiness Of Protected Forest Buffer Villages In Eastern Kalimantan (Case Study: Wain River Protected Forest) - Hudthaibah, Hudthaibah; Makkarateng, Makkarateng; Suprapto, Thotok; Paselle, Enos (UNIVERSITAS PAKUAN, 2025)
Climate change and ecological pressures such as forest fires, land conversion, and natural resource degradation have a significant impact on the sustainability of the lives of protected forest buffer village communities in East Kalimantan. This research aims to assess the social-ecological readiness of the community in facing these pressures and design an adaptive and contextual community-based strategic model, with a case study of the Sungai Wain Protection Forest (HLSW). The method used was a mixed-methods approach consisting of three main techniques: (1) household survey of 200 respondents from two villages (RT 38 Karang Joang Village (Sungai Wain Village) and Lamaru Village) directly adjacent to the HLSW area, (2) focus group discussions (FGDs) and in-depth interviews with 30 key informants from village government, customary, NGOs, and forestry agencies, and (3) social ecological mapping using a participatory approach with the help of GIS technology. The results identified three clusters of community readiness, namely: “strong adaptive”, “transition moderation”, and “ecologically vulnerable”. Villages active in social forestry programs and involved in initiatives such as ProKlim and Green Growth Compact showed better economic and institutional readiness than villages dependent on traditional agriculture. This research has led to the development of community-based adaptation strategies that can be adopted by other forest buffer villages in Indonesia. This approach can increase the effectiveness of policy interventions within the framework of locally-based natural resource management and disaster risk reduction.